2020
DOI: 10.1002/iid3.367
|View full text |Cite
|
Sign up to set email alerts
|

Evidence and implications of pre‐existing humoral cross‐reactive immunity to SARS‐CoV‐2

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has emerged throughout the world. Building knowledge around Covid‐19 is crucial to devise facts based approaches to respond efficiently against this pandemic. Aim We aimed to investigate pre‐existing humoral cross‐reactive immunity to SARS‐CoV‐2. Method We have tested the reactivity against SARS‐CoV‐2 nucleocapsid (N) antigen of sera collected from healthy healthcare volunteers in 2014. We assessed immunoglobulins reactive against SARS‐CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…As we confirmed the sensitivity of PBNA, high background levels (PBNI 50 of 100 to 250) in 5 out of 6 unexposed NHP serum samples, might be due to pre-exposure to other coronaviruses in their natural environment (which might have generated neutralizing antibodies). Couple of previous reports about preexisting humoral immunity to SARS-CoV-2 in humans support this explanation [31,32].…”
Section: Discussionsupporting
confidence: 63%
“…As we confirmed the sensitivity of PBNA, high background levels (PBNI 50 of 100 to 250) in 5 out of 6 unexposed NHP serum samples, might be due to pre-exposure to other coronaviruses in their natural environment (which might have generated neutralizing antibodies). Couple of previous reports about preexisting humoral immunity to SARS-CoV-2 in humans support this explanation [31,32].…”
Section: Discussionsupporting
confidence: 63%
“…As we confirmed the sensitivity of the PBNA, high background levels (PBNI 50 of 100 to 250) in five out of the six unexposed NHP serum samples might be due to pre-exposure to other coronaviruses in their natural environment (which might have generated neutralizing antibodies). Several previous reports regarding preexisting humoral immunity to SARS-CoV-2 in humans support this explanation [31,32].…”
Section: Discussionmentioning
confidence: 79%
“…Findings from previous studies using samples from Benin, Nigeria, and Ghana have led to speculation that malaria contributes to cross-binding antibodies or other humoral factors (19,20). An additional study in the country of Gabon, where malaria is highly endemic, found that 32 of 135 (23.7%) samples from 2014 were positive for SARS-CoV-2 antibodies using an NCP antigen serological assay, although the authors acknowledged that the cause of the cross-reactivity could not be isolated with certainty (37). Our current study found anti-Plasmodium IgG levels to be significantly higher in samples with false-positive SARS-CoV-2 results than in those with negative results.…”
Section: Discussionmentioning
confidence: 99%